Alterations in B Cell Compartment Correlate with Poor Neutralization Response and Disease Progression in HIV-1 Infected Children - Aggarwal, Heena; Khan, Lubina; Chaudhary, Omkar; Kumar, Sanjeev; Makhdoomi, Muzamil Ashraf; Singh, Ravinder; Sharma, Kanika; Mishra, Nitesh; Lodha, Rakesh; Srinivas, Maddur; Das, Bimal Kumar; Kabra, Sushil Kumar; et al. (Frontiers in Immunology, 2017)
Several B cell defects are reported in HIV-1 infected individuals including variation in B cell subsets, polyclonal B cell activation and exhaustion, with broadly neutralizing antibodies (bnAbs) elicited in less than 10-20% of the infected population. HIV-1 disease progression is faster in children than adults. B lymphocyte stimulator (BLyS), expressed on dendritic cells (DCs) is a key regulator of B cell homeostasis. Understanding how DCs influence B cell phenotype and functionality (viral neutralization), thereby HIV-1 disease outcome in infected children is important to develop interventional strategies for restoration of B cell function. In this study, a total of 38 vertically transmitted HIV-1 infectedantiretroviral therapy (ART) naïve children and 25 seronegative controls were recruited. Based on the CD4 counts and years post infection, infected children were categorized as long term non-progressors (LTNPs) (n=20) and progressors (n=18). Eight of these progressors were followed up at 6 to 12 months post ART. Percentages (%) of DCs, B cell subsets and expression of BLyS on DCs were analyzed by flow-cytometry. Plasma levels of B cell growth factors were measured by ELISA and viral neutralization activity was determined using TZM-bl assay. Lower (%) of myeloid DCs, plasmacytoid DCs and high expression of BLyS on myeloid DCs were observed in HIV-1 infected progressors than seronegative controls. Progressors showed lower % of resting memory B cells and higher % of mature activated, tissue like memory B cells as compared to seronegative controls. Higher plasma levels of IL-4, IL-6, IL-10, and IgA were observed in progressors vs. seronegative controls. Plasma levels of IgG were high in progressors and in LTNPs than seronegative controls, suggesting persistence of hyper-gammaglobulinemia at all stages of disease. High plasma levels of BLyS in progressors positively correlated with poor viral neutralizing activity. Interestingly on follow up, treatment naïve progressors, post ART showed increase in resting memory B cells along with reduction in plasma BLyS levels that correlated with improvement in viral neutralization. This is the first study to demonstrate that reduction in plasma BLyS levels correlates with restoration of B cell function, in terms of viral neutralization in HIV-1 infected children.